The challenges experienced by student teachers during the height of the COVID-19 pandemic in their teaching practice - Tshiovhe, T. E. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Student teachers must cultivate the capacity to amalgamate their educational insights by engaging in a blend of academic and practical endeavours. Work Integrated Learning (WIL) within Higher Education Institutions serves as a pivotal component of undergraduate programs, emphasizing student-centred learning approaches. WIL is formally integrated into degree courses, validated through assessment criteria, and awarded credit points. The execution of teaching practice must be hands-on to translate theoretical knowledge into practical application. In light of the context, as mentioned earlier, this paper scrutinizes the obstacles encountered by student teachers amid the apex of the COVID-19 pandemic in their teaching practice. Departing from the constructivist research paradigm, a qualitative methodology is employed. Data acquisition entailed conducting in-depth interviews with participants, with purposive sampling guiding the selection of student teachers. Ten (10) fourth years studying Bachelor of Education in Further Education (BEDFET) student teachers served as key informants for this investigation. Thematic analysis of the data was conducted in alignment with the study's research objectives. The discourse underscores the imperative for the continuity of teaching practice even in the face of potential future pandemics.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 2, Volume 9, 2025
Keywords: Assessment; Covid -19; Student teachers; Student-centred Learning; Teaching practice; Work-integrated Learning; Teaching; Blended learning; Computer-assisted instruction; COVID-19 (Disease); Student teachers; Education, Higher